Improvements in self-consolidating cementitious composites by using micro carbonized aggregates - Giuseppe Andrea Ferro; Sajjad Ahmad; Rao Arsalan Khushnood; Luciana Restuccia; Jean Marc Tulliani (Fracture and Structural Integrity)
There is growing interest in the use of self-consolidating cementitious systems in construction industry. The present research was conducted to enhance the mechanical performance of cement composites by the utilization of micro-sized inert particles. This paper deals with the synthesis of micro-sized inert carbonized particles from hemp hurds. The synthesized carbonized particles were characterized by field emission scanning electron microscope (FESEM). These particles were further used as additive in self-consolidating cement composites. Total of four different wt% additions (i.e. 0.08, 0.20, 1.00 and 3.00 by wt% of cement) were investigated. The cement composites containing carbonized particles inclusions were characterized by three point bending and compression tests. The results indicate that the carbonized particles additions enhanced the flexural and compressive strengths of the cement composites. It was also observed that the fracture properties and the energy absorption capability of the cement composites were enhanced substantially.